Medidas de torção com redes de Bragg gravadas em fibras óticas de alta birrefringência - Grabski, Elaine Cristina (2022)
The main objective of the present work is the torsional characterization of Bragg gratings recorded on high birefringence (HiBi) optical fibers (FBGs). The research involves the characterization by torsion tests of Bragg gratings recorded on different types of high birefringence optical fibers and the comparison of the sensitivities obtained in the different measurements. The work reports on recordings of the Bragg gratings on different types of high birefringence fibers; the spectral characterization of the devices by torsion; the coating of the sensors with a metallic material and the comparison of the torsion results with and without the encapsulation. The results obtained show that an analysis of FBGs in different types of HiBi fibers can be used for the comparison of torsional sensitivities. Using the different spectra, the intensities of the reflection peaks as a function of the rotation angle can be obtained. Different high birefringence optical fibers can lead to different sensitivities and results in response to torsion, which may be related to stress and birefringence induced in a complex way.